Biologics for psoriasis patients under 18 years of age: Real-world evidence from the Chinese psoriasis real world evidence research group - Zheng, Yu-Xin; Ye, Li-Ran; Yan, Bing-Xi; Chen, Si-Qi; Cai, Sui-Qing; Man, Xiao-Yong (Frontiers in Medicine, 2022)
Background: Treatment for pediatric psoriasis is challenging because of the lack of real-world evidence, especially for biological therapies. Objectives: This study evaluated the efficacy and safety of biologics in children with psoriasis based on real-world evidence. Methods: Pediatric psoriasis patients aged <18 years who were treated with biologics in our hospital (2020–2022) were prospectively analyzed. Patients treated with adalimumab, secukinumab, or ixekizumab were followed up for at least 16 weeks, and 22 of 38 patients completed the 52-week observation period. Dermatologist raters were blinded to ensure the reliability of the PASI, BSA, and PGA score assessments. PASI 75 or PGA 0/1 at week 12 represented an efficient indicator. Results: Thirty-eight patients (20 males and 18 females; median age, 12.6±4.1 years) were enrolled, and none were lost to follow-up. All participants were diagnosed with psoriasis, including plaque psoriasis (n=36), nail psoriasis (n=1), and pustular psoriasis (n=1). Within 12 weeks, all patients achieved scores above PASI 75 and PGA 0/1. The average time to reach PASI 75 was 4.3±2.0, 3.2±1.8, and 2.4±0.4 weeks in patients using adalimumab, secukinumab, and ixekizumab, respectively, and, 27.2% (3/11), 86.4% (19/22), and 75.0% (3/4) of these patients achieved PASI 100 at week 12, respectively. Moreover, 18 of 20 patients with plaque psoriasis maintained ≥PASI 75 after 52 weeks. The most commonly reported adverse effect was upper respiratory tract infection, and no severe adverse effects were reported. Conclusions: Our real-world data demonstrated the safety and effectiveness of adalimumab, secukinumab, and ixekizumab in children with psoriasis.